IDENTIFICATION OF PHARMACEUTICAL PRODUCTS IN ACCOUNTING SYSTEM: PROBLEMS OF HARMONIZATION - M. I. Skrypnyk; I. M. Vyhivska; I. L. Grabchuk; O. O. Hryhorevska (Фінансово-кредитна діяльність: проблеми теорії та практики)
In the article it is set a problem of substantiation of the essence and components of pharmaceutical products as an object of accounting on the basis of comparison of existing international and national classification standards, which will facilitate the improvement of accounting of pharmaceutical products. In the research process there were used methods of observation, comparison, analysis, synthesis, generalization and econometric-statistical method. In the article it is defined the list of components of pharmaceutical products based on the analysis of regulations of existing normative documents (the Law of Ukraine “On Medicines”, the Ukrainian Classification of Goods for Foreign Economic Activity (UCGFEA), which is the commodity nomenclature of  Customs Tariff of Ukraine (CTU is based on the Harmonized System of Description and Coding of Goods of the World Customs Organization and the Combined Nomenclature of EU), “Classifications of Types of Economic Activities” (SC 009: 2010, CTEA-2010)). It was established that under pharmaceutical goods as an object of accounting should be understood the goods, finished products, raw materials and materials, semi-finished products and component parts, semi-finished products of own production and customary raw materials intended for sale (production, processing) by the entities of pharmaceutical market in accordance with the requirements and standards of state and international levels in the field of pharmacy. The components of pharmaceutical products are harmonized in accordance with the domestic classifiers of activities and individual entity of accounting: (goods, finished products, raw materials and materials, semi-finished products and component parts, semi-finished products of own production and customary raw materials intended for sale (production, processing) by entities of pharmaceutical market in accordance with the requirements of state and international standards in the field of pharmacy). It is substantiated that they are attributed to certain groups of accounting accounts. The proposals provide the improved pharmacy management accounting and minimize its manufacturing and commercial risks.